Himma K. E. The Logic of Showing Possibility Claims: A Positive Argument for Inclusive Legal Positivism and Moral Grounds of Law / trans. from English V. V. Ogleznev, D. V. Shvedov - V. V. Ogleznev; D. V. Shvedov (Омский научный вестник: Серия "Общество. История. Современность")
In this essay, I argue for a view that inclusive positivists share with Ronald Dworkin. According to the Moral Incorporation Thesis (MIT), it is logically possible for a legal system to incorporate moral criteria of legality (or ‘grounds of law’, as Dworkin puts it). Up to this point, the debate has taken the shape of attacks on the coherence of MIT with the defender of MIT merely attempting to refute the attacking argument. I give a positive argument for MIT. I begin with an explanation of the logic of establishing possibility claims, such as MIT. At the outset, it is worth noting that the logic of establishing possibility claims is very different from the logic of establishing contingent descriptive claims or necessary claims. For this reason, some explication of the relevant features of the semantics of modal logic will be necessary here. Once the structural framework is adequately developed, the argument for MIT will be grounded on the strength of a thought experiment of a surprisingly simple kind. Indeed, the argument is inspired by a Razian argument for the possibility of a legal system without coercive enforcement machinery; on his view, a society of angels could still have a system of law without any coercive machinery. My argument will possess two theoretically important qualities that are also possessed by Raz’s powerfully simple, but ultimately unsuccessful, argument.